Budget Policy in 2019–2021: Between Scilla and Charibda - O. A. Grishina; V. A. Slepov; A. Yu. Chalova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzes the federal budget for 2019–2021 and principle tools of pursuing budget policy of the Russian Federation.  It assessed transformation of the budget policy model in the mentioned period, which aims at shaping the finance system able to counteract external shocks in the form of growing sanctions against Russia, foreign-economic conflicts among key players of the global market, uncertainty in international policy and economy. At the same time budget policy is oriented towards creating necessary conditions to speed up the growth rate of Russian economy and improve wellbeing of the Russian population. The authors estimate the key mechanism of the current budget policy in Russia, which can provide balance of the federal budget, i.e. the budget rule. It was grounded that the effective model of the budget rules aimed at accumulation of budget resources and their limited use in the field of end services for the population could create risks of low impact of budget expenses on factors of economic growth in Russia, hinder realization of the natural mechanism of increasing profits of the federal budget at the expense of onward development of economy. In this connection it is necessary to alter the medium-term concept of budget policy by re-orienting its tools towards target growth in real population income and investment in fixed capital but not only towards volumes of accumulated reserves and proficiency of the federal budget.